PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN WORDWALL UNTUK MENINGKATKAN LITERASI NUMERASI PADA MATERI BILANGAN CACAH SISWA KELAS V SDN GADANG 4 - Dian Mirosa, Yuvita; Dwi Ferdian, Rosita; Sulistyo; Kukuh, Andriyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students numeracy literacy skills through the implementation of the Problem Based Learning (PBL) model assisted by Wordwall on whole number material in Grade V of SDN Gadang 4. This research is a Classrom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and refclection stages. The research subject were 27 students. Data were collected through tests, observations, amd questionnaires, and analyzed using descriptive quantitative and qualitative methods. The result showed that the implementation of the PBL model assisted by Wordwall was able to improve students numeracy literacy skills. This is indicated by the increase in learning mastery from 22,22% in the pre-cycle to 55,56% in cycle I, and further increased to 85,19% in cycle II. In addition, student learning activities improved from 52,5% to 92,5%. Numeracy literacy skills based on observation also increased from 62,5% to 93,75%. Therefore, the implementation of the Problem Based Learning (PBL) model assisted by Wordwall is effective and meaningful learning.